“Kearifan Lokal Dalam Perspektif Kebijakan Sumberdaya Manusia (SDM) Pemerintahan Desa” (Studi di Desa Palaan, Kecamatan Ngajum, Kabupaten Malang) - Mashur Hasan Bisri (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
Law Number 6 of 2014 concerning villages as an affirmative policy so that villages can carry out various forms of development in all fields, both the village government sector, the village development implementation sector, the village community development sector, and the village community empowerment sector. So that villages can freely shape themselves and their respective images in accordance with the identity of the villaget. The research was conducted using qualitative methods through, namely: 1. Primary data 2. Secondary data. It can be through documents, reports and other sources that have relevance to the object of research, namely data that is already available in Palaan Village, Ngajum District, Malang Regency. is supporting data obtained indirectly by informants.The results of this study are that the role of local wisdom in Palaan village with the ongoing development of the village community will have a very significant relationship. This has become part of the customary beliefs and traditions that have developed in society so far, so that preservation is needed for future continuation, as modernization continues to develop. Local wisdom that is cultural in nature such as traditional ceremonies is carried out in the context of pre-implementation of activities for infrastructure development, while the values ​​contained in this culture have not received a formal budget portion in the Village Revenue and Expenditure Budget (APBDes) in Palaan Village